2019
DOI: 10.3233/jad-190587
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Salivary Microbiome in Patients with Alzheimer’s Disease

Abstract: Recent studies found that poor oral hygiene was associated with increased risk of dementia, and the number of oral bacteria significantly increased in the brain tissues of patients with Alzheimer's disease (AD), suggesting that the oral microbiota may play an important role in the pathogenesis of AD. However, the actual composition of oral bacteria communities in patients with AD and whether these oral bacteria are associated with disease severity remain largely unknown. Also, the APOE 4 polymorphism is a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 41 publications
5
71
0
Order By: Relevance
“…A nationwide, retrospective, matched-cohort study in Taiwan showed that patients with chronic periodontitis and gingivitis have a higher risk of developing dementia compared to those with healthy gums (Tzeng et al, 2016). Moreover, recent accumulating evidence has demonstrated a causal relationship between oral microbiome and AD (Paganini-Hill et al, 2012;Harding et al, 2017;Liu et al, 2019b;Panza et al, 2019;Olsen and Singhrao, 2020). For example, P. gingivalis, the most common periodontal bacteria causing periodontal disease, was capable of inducing accumulation of amyloidbeta plaques and neurofibrillary tangles following experimental oral infection in mice (Dominy et al, 2019).…”
Section: Oral Microbiome and Alzheimer's Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…A nationwide, retrospective, matched-cohort study in Taiwan showed that patients with chronic periodontitis and gingivitis have a higher risk of developing dementia compared to those with healthy gums (Tzeng et al, 2016). Moreover, recent accumulating evidence has demonstrated a causal relationship between oral microbiome and AD (Paganini-Hill et al, 2012;Harding et al, 2017;Liu et al, 2019b;Panza et al, 2019;Olsen and Singhrao, 2020). For example, P. gingivalis, the most common periodontal bacteria causing periodontal disease, was capable of inducing accumulation of amyloidbeta plaques and neurofibrillary tangles following experimental oral infection in mice (Dominy et al, 2019).…”
Section: Oral Microbiome and Alzheimer's Diseasementioning
confidence: 99%
“…In addition, there is data indicating the significant differences in quantity and quality of oral microbiome in AD patients compared to mentally healthy individuals of the same age. For example, Liu et al have demonstrated lower richness and diversity of salivary microbiome in patients with Alzheimer's disease compared to healthy controls (Liu et al, 2019b). The authors reported a relatively high level of Moraxella, Leptotrichia, and Sphaerochaeta and significantly decreased number of Rothia in the saliva of AD patients (Liu et al, 2019b).…”
Section: Oral Microbiome and Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, oral bacteria have been frequently observed in the AD brain tissue compared with normal controls suggesting possible roles of oral microbiome in pathogenesis of AD (18,19). Recently, salivary microbiome in AD patients showed reduced diversity compared with healthy controls (20). Oronasal cavity is close to brain and has associated with the brain via the trigeminal and olfactory nerves (21).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, dysbiotic oral microbiome has been suggested to increase the infection of opportunistic pathogens in the brain of AD patients and further contribute to the development of AD (18,22). Few studies have been conducted to characterize the oral microbiome in AD (20). Moreover, there is no study that has focused on CP patients with AD.…”
Section: Introductionmentioning
confidence: 99%